Impoving energy characteristics of the welding power sources for TIG-AC welding - Burlaka, Vladimir; Lavrova, Elena (Eastern-European Journal of Enterprise Technologies, 2019)
This paper proposes a circuit solution and a control algorithm for a welding power source for TIG-AC welding with improved energy characteristics. The source is made using a welding transformer and a low-voltage series active power filter on power field effect transistors with a low channel resistance. The transformer used can be with normal or increased leakage. The proposed source is characterized by improved technical parameters due to the possibility to form V-I characteristic with the required stiffness without switching the welding transformer taps. Control scheme ensures the elimination of a DC component of welding current during a TIG-AC process; it is also possible to control the waveshape of a welding current. Also, a "soft" arc ignition based on the Lift-Arc principle is provided, which positively affects the service life of a non-fusible electrode. The developed source is distinguished by a possibility to work in a reactive power compensation mode. This reduces the consumption of reactive power by electrical complexes with welding power sources and reduces a current loading on the distribution network. Application of the proposed principle to construct a source for arc welding with an alternating current makes it possible to modernize existing transformer sources by installing an active power filter unit in them. That would improve consumer properties of the sources by improving the stability of a welding arc, by smooth regulation of welding current, reducing the effects of a network voltage fluctuations on quality of the welding process. It eliminates the need to apply ballast resistors for adjusting a welding current, as well as the block of capacitors to eliminate the magnetization of a transformer during the TIG-AC process. The proposed source could be used not only to implement TIG-AC, but the MMA, MIG, MAG alternating current welding processes